Delayed Bitterness of Citrus Wine Is Removed Through the Selection of Fining Agents and Fining Optimization - Bi, Jingying; Li, Hua; Wang, Hua (Frontiers in Chemistry, 2019)
“Delayed bitterness” (DB) in citrus wine is caused by limonoids and determines the acceptability to consumers. In this study, a variety of fining agents, specifically gelatin, agar, chitosan, bentonite, the crosslinking agent polyvinylpyrrolidone (PVPP), diatomite, and casein, were evaluated for their ability to lower DB in citrus wine. Factorial experiments with three factors at four levels (L34) and with two factors at three levels (L23) were used to determine the optimal effect. We found that a mixture of agar (125 mg/L) and gelatin (30 mg/L) not only decreased the limonoid concentration and clarified the liquor, but also increased the precipitation content, retention rate of ascorbic acid, and antioxidant capacity. After treatment, the quality of the citrus wine was improved, and a few volatile chemical compounds were lost. We determined that agar and gelatin were the best fining agents for reducing DB in citrus wine.